Study of Virulence Factors in Urease-Positive Bacteria Isolated from Urinary Tract Infections Clinical Specimens - Ali S. Dheyab; Omar I. Aljumaili; Najeeb M. Hussein (Journal of Pure and Applied Microbiology, 2018)
The study included investigation virulence factors that product from urease positive bacteria species isolated from urinary tract infection. a total of 60 clinical specimens, taken from urine sample had been cultured and identified pure isolates result show like Klebsiella. pneumonia (n = 5, 8.3%), Staphylococcus.sp (n = 3, 5%) and Pseudomonas.aeruginosa (n = 1, 1.6%). Most isolated of urease positive bacteria were negative gram stains excepted Staphylococcus sp. was positive gram stain. All isolates gave positive result of catalase test, while coagulase, oxidase, indole, Simmon citrate and kligler test was performed for all isolated gave variable result. Also all urease positive bacteria were identified by using VITEK-2 system. Klebsiella.pneumonia, Staphylococcus.aureus and Pseudomonas.aeruginosa non fermentation for lactose sugar test while Staphylococcus.Saprophyticus had ability lactose fermentation. Antibiotic susceptibility for all urease positive bacteria results showed that all highly sensitive towards (Amikacin, Gentamycin, Imipenem, Norfloxacin, Ciprofloxacin and Vancomycin) while showed low sensitivity towards (Ceftriaxone, Cefotaxime, Nalidixic acid and Nitrofurantoin). In addition all bacteria produce urease showed had Clear difference in another virulence factors like (DNase, Lipase, Protease).